Analysis of Student Interest in Using Sharia Bank Mobile Banking with Conventional Banks - Yuni Pramita; Mutiara Cantika Sari (Sharia Economic and Management Business Journal (SEMBJ), 2022)
. This research aims to determine the interest of UINFAS Bengkulu students in using mobile banking at Sharia banks and conventional banks. This research aims to increase students' interest in becoming users of its services. This research uses qualitative methods using interview data from students at UINFAS Bengkulu. From the results of this research, it can be concluded that the main factor in student interest is the accessibility of banking which is easy to reach.